2018
DOI: 10.3892/mmr.2018.9631
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‑rich medium alleviates high glucose‑induced oxidative stress and parthanatos in rat Schwann cells in�vitro

Abstract: Diabetic peripheral neuropathy (DPN) is considered to be the most common cause of microvascular diabetic complications, for which no effective therapies currently exist. Previous studies have identified that oxidative stress is the common pathway in all possible hypotheses for the induction of DPN, and poly(ADP-ribose) (PAR) polymerase-1 (PARP-1)-dependent cell death (parthanatos) is key in the pathogenic mechanisms of neurodegenerative disease. The aim of the present study was to investigate the protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In the present study, HS treatment resulted in a reversal of the lower paw withdrawal threshold and a reduction of MNCV deficiency in diabetic rats. Oxidative stress is one of the main causes of the complex pathophysiology of DPN (1,7). Previous studies have indicated that hyperglycemia increases the production of free radicals by increasing intracellular glucose oxidation, which subsequently results in neurotoxicity (7).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, HS treatment resulted in a reversal of the lower paw withdrawal threshold and a reduction of MNCV deficiency in diabetic rats. Oxidative stress is one of the main causes of the complex pathophysiology of DPN (1,7). Previous studies have indicated that hyperglycemia increases the production of free radicals by increasing intracellular glucose oxidation, which subsequently results in neurotoxicity (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the details of HS preparation (7,18). At 0.4 MPa, H2 was dissolved in normal saline for 6 h, until it reached supersaturation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations